Sosialisasi dan Promosi Pemilihan Program Studi di Kampus ITB Riau Pesisir untuk Pelajar di Kelurahana Tanjung Penyembal Kota Dumai - Muhammad Arif; Rudi Faisal; Soni Fajar Mahmud; Elisa Hafrida (Indo Publishing, 2026)
The low level of access and interest among secondary school students in pursuing higher education in the region remains a challenge to improving the quality of human resources. One of the main factors is a lack of information regarding study programme options, university admission routes, and scholarship opportunities. This community service activity aims to increase knowledge and foster interest among secondary school students in Tanjung Penyembal Sub-district to continue their studies at university, specifically at the Riau Pesisir Institute of Technology and Business in Dumai City. The methods employed were outreach and promotion of higher education through an educational-participatory approach, which included campus tours, presentations on study programmes, guidance on admission pathways to state universities, alumni sharing sessions, and the distribution of promotional materials. Evaluation was conducted using pre- and post-activity interest questionnaires, observation, and brief interviews. The results of the activity showed a significant increase in students’ understanding of the study programmes available at ITB Riau Pesisir, as well as scholarship opportunities. Furthermore, there was an increase in students’ interest in pursuing higher education after attending the outreach session. This activity also succeeded in building positive communication and partnerships between the university and partner schools in the area within the Tanjung Penyembal neighbourhood.